Sektor Pembangkit Perekonomian Kabupaten Hulu Sungai Tengah Selama Pandemik COVID-19 - Arif Maulana; Nugrahayu Suryaningrum (Jurnal Kebijakan Pembangunan, 2021)
The Covid-19 pandemic has spread out in Indonesia include in Hulu Sungai Tengah Regency. In 2020, this pandemic caused a deep economic contraction that needs to be a concern for local governments. This study aims to determine the potential sectors of the Hulu Sungai Tengah Regency during the Covid-19 pandemic to be able to rise from economic contraction. The data used are sourced from BPS-Statistics including Gross Regional Domestic Product at constant prices 2010 by industry, PDRB at current prices by industry, population, the share of economic sectors, Economic Growth during 2016-2020. The analysis used was Typology Klassen Analysis and Location Quotient which resulted that the Agriculture, Forestry, and Fisheries; Information and Communication sectors becoming the potential sectors that lead the economy of Hulu Sungai Tengah Regency during the Covid-19 pandemic. Based on information technology and focus on potential sectors, the growth of other sectors such as Manufacturing; Trading; Accommodation, Food, and Beverage will grow to increase the added value of the regional economy of Hulu Sungai Tengah Regency.